Sistem Pengarsipan Surat Masuk dan Surat Keluar pada Sar Hnc Lanud Adi Soemarmo - Fajar Yahya (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
This web-based incoming and outgoing mail archiving information system was built to facilitate the work process in managing incoming and outgoing mail archives, especially in the field of archiving at the SAR HNC Adi Soemarmo Airport which is intended to further streamline computerized data processing and support technical implementation in carrying out data processing. easier, faster, and more efficient mail. Letters are tools or means to convey written statements or information from one party to another. Such information can be in the form of notices, statements, requests, reports, disclaimers, thoughts, questions, and so on. Letters are often used by companies or organizations because letters act as reminders and as documentation material for every process, both internal and external. Making a computerized system for filing incoming and outgoing mail at the SAR HNC Adi Soemarmo Air Base through several stages. The advantages of this system, among others, are as a modern and website-based mail archiving tool that simplifies and eases the work of the letter archiving process compared to the manual method that is already running.